ANALISIS LOCATION QUOTIENT (LQ) DALAM PENENTUAN LOKASI BASIS TANAMAN CABAI RAWIT (Capsicum Frutescens L) DI PROVINSI ACEH - Lilian Natasya; Muhammad Jamil; Cut Gustiana (Bajang Institute, 2025)
This study aims to determine the location of the Capsicum frutescens, L. plant base in districts/cities in Aceh Province. The data collection method is a survey method based on secondary data obtained from the Central Bureau of Statistics of Aceh Province. The research design used in this research is quantitative descriptive. For the location of the Capsicum frutescens, L base in Aceh Province, Location Quotient (LQ) analysis was used. The data used is the population of horticultural plant species in Aceh Province in 2013-2022. The results of this study indicate that there are 3 districts that have base potential in cayenne pepper production, namely Central Aceh District, Bener Merah District and Gayo Lues District. There are several Regencies/Cities that have no potential in cayenne pepper production, namely Simeulue District, South Aceh District, Southeast Aceh District, East Aceh District, West Aceh District, Aceh Besar District, Pidie District, Bireuen District, North Aceh District, Southwest Aceh District. , Aceh Tamiang Regency, Nagan Raya Regency, Aceh Jaya Regency, Pidie Jaya Regency, Banda Aceh City, Sabang City, Langsa City, Lhokseumawe City, Subussalam Regency. And only 1 district has the opportunity to produce cayenne pepper for the next few years, namely Aceh Singkil district.